PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PO. JASA MALINDO TRAYEK SOLOK - PADANG - Febria Purwasih, Vivi; Masrin, Indra; Hidayat, Rian (Pendidikan Ekonomi, 2014)
ABSTRACT                   Marketing Mix Influence Consumer Buying Decision Against the trajectory Malindo PO.Jasa Solok - Padang , This study aims to determine whether the marketing mix affect consumer purchasing decisions at the PO . Malindo services Solok - Padang route . This type of research is survey research , where the research was carried out on a number of units of analysis that found the facts or factual information about the symptoms of a group or individual behavior and the results can be used as materials for planning or decision-making . The population in this study were all passengers Freight PO.Jasa Malindo Solok - Padang route . The sampling technique used was non- probability sampling using purposive sampling techniques , namely the determination of the sample based on certain considerations , the data collection techniques used by distributing questionnaires . The sample used by 80 of the respondents were already using a PO . Malindo services Solok - Padang route at least three times . Analysis tools used are validity , reliability test , normality test, multicollinearity , multiple linear regression , t test , F test , and test the coefficient of determination ( R2 ) . The results showed that 70 % variable purchase decisions are influenced by the independent variables are: Product ( X1 ) , price ( X2 ) , promotion ( X3 ) , distribution ( X4 ) , people / employees ( X5 ) , process ( X6 ) and Physical Evidence ( X7 ) . While the remaining 30 % of purchase decisions are influenced by other variables that are not included in this study . T-test research results ( partial ) product ( X1 ) with a significant value of 0.41 , the price ( X2 ) with a significant value of 0.41 , promotion ( X3 ) with a significant value of 0.30 , the distribution ( X4 ) with significant values of 0.40 , the ( X5 ) with a significant value of 0.09 has no effect on consumer purchasing decisions , while the process ( X6 ) with significant value sebesar0 , 02 , physical evidence with a significant value of 0.00 can be said process and physical evidence influence on consumer purchase decisions and test f ( simultaneous ) indicates that the product ( X1 ) , price ( X2 ) , promotion ( X3 ) , distribution ( X4 ) , people / employees ( X5 ) , and physical evidence ( X7 ) significantly affect consumer purchasing decisions at the PO . Malindo services Solok - Padang route .